2021
DOI: 10.1186/s12903-021-01702-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dental caries increment using salivary biomarkers in a remote Indigenous Australian child population

Abstract: Background The burden of childhood dental caries amongst Indigenous Australians is higher than in other Australians. Because of differences in lifestyle and the evolutionary history of the oral microbiota, associated risk indicators may differ. Here, we evaluate associations between caries increment, salivary biomarkers and baseline caries among children aged 5–17 years residing in a remote rural Indigenous community. Methods This study was part of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These findings are consistent with previous studies that have highlighted the clinical importance of these factors in predicting caries risk. [ 4 21 , 22 ] Chaffee et al . [ 23 ] conducted a retrospective cohort study using data collected from electronic records at the university instruction clinic to assess the risk factors associated with future caries.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies that have highlighted the clinical importance of these factors in predicting caries risk. [ 4 21 , 22 ] Chaffee et al . [ 23 ] conducted a retrospective cohort study using data collected from electronic records at the university instruction clinic to assess the risk factors associated with future caries.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has been reported that when the S. mutans levels in saliva are above 10 5 cfu mL −1 , there is a significant risk of severe damage to dental hard tissues, which can accelerate the development of dental caries. 6,7 As such, S. mutans can be used as a general bacterial marker to predict dental caries. A series of in-mouth devices have been fabricated to detect S. mutans levels in saliva for evaluating dental caries.…”
Section: ■ Introductionmentioning
confidence: 99%